Serial quantitative angiographic study of target lumen enlargement after drug‐coated balloon angioplasty for native coronary artery disease. Issue 4 (25th February 2023) - Ueno, Katsumi; Morita, Norihiko; Kojima, Yoshinobu; Takahashi, Hiroshi; Esaki, Masayasu; Kondo, Hiroki; Ando, Yu; Yamada, Mayu; Kosokabe, Tai
Abstract: Background: Target lumen enlargement (TLE) or "late lumen enlargement" is often encountered after percutaneous coronary intervention (PCI) with drug‐coated balloons (DCB). To date, the prognosis of coronary arterial lesions with or without TLE has not been clearly elucidated. Aims: This study aimed to assess the long‐term prognosis of coronary arterial lesions with or without TLE observed within 1 year (early TLE) after DCB angioplasty using serial quantitative angiographic follow‐up. Methods: One hundred and ninety‐three consecutive patients (de novo coronary arterial lesions, 251) who underwent follow‐up angiography within 1 year after DCB angioplasty (early follow‐up, median: 6 months) were retrospectively evaluated. Of these, 97 patients (125 lesions) also underwent angiography more than 1 year after DCB angioplasty (late follow‐up, median: 37 months). TLE was defined as an increase in minimal lumen diameter (MLD) after PCI at each follow‐up. Results: Early TLE was detected in 142 lesions (56.6%). Of these, 76 lesions were also evaluated at late follow‐up. TLE persisted even at late follow‐up in 67 of the 76 lesions (88.2%). An increase in MLD in early TLE (+) lesions was observed in the period between post‐PCI and early follow‐up (1.84 ± 0.06 vs. 2.12 ± 0.07 mm, p  < 0.001) but not between early and late follow‐up (2.12 ± 0.07 vs. 2.16 ± 0.07 mm, p  = 0.74). In contrast, 49 of 109 lesions without early TLE were evaluated at late follow‐up, of which 28 lesions (57.1%) showed TLE at late follow‐up. The MLD of early TLE (−) lesions ( n  = 49) significantly increased from early (1.63 ± 0.061 mm) to late follow‐up (1.84 ± 0.06 mm) ( p  < 0.001). No aneurysms were found in any of these cases. Conclusion: Early TLE was observed in more than half of the lesions, with the majority remaining at late follow‐up. Alternatively, half of the lesions without early TLE showed late TLE, occurring biphasically after DCB angioplasty.